Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Berbasis Web Pada STMIK Primakara - Ni Komang Arix Purnama; A.A Istri Ita Paramitha; Ni Made Estiyanti (Primakara University, 2020)
STMIK Primakara is aInformatics and Computer College which of course cannot be separated from the existence of computerization. Most of the systems that are there are already computerized, including the processing of financial data. Where financial data processing, there is a process of cash receipts and payments like companies in general. This study discusses the development of an information system for cash receipts and disbursements at STMIK Primakara. This researchwas conducted using the Linear Sequential method. This research uses the PHP programming language with a code igniter framework. This research succeeded in developing a cash management information system, especially cash receipts and disbursements at STMIK Primakara. From the results of interviews with users conducted by researchers, responses from those who will use this system are quite positive because it canfacilitate them in the process of managing financial data.